DAMPAK KESEJAHTERAAN GURU TERHADAP MOTIVASI DAN KINERJA MENGAJAR DI SMA 11 SURABAYA - Lina Mai Afinda Sari; Lilis Avrilia Devianti, Marsya Firanda Putri, Syunu Trihantoyo, Nuphanudin (CV. ADIBA AISHA AMIRA, 2025)
This article discusses the importance of using technology and innovative learning methods in improving the effectiveness and efficiency of learning at SMAN 11 Surabaya. The use of innovative learning offline is carried out with various creative strategies that have had a positive impact on student motivation, understanding, engagement, and learning ability. In addition, various learning methods also help teachers in achieving learning objectives optimally, but funding constraints that are not in accordance with the program schedule are the main obstacles in developing teacher professionalism in teaching. This research method uses a skinative approach by collecting primary data through interviews, observations, and documentation. The level of attendance and engagement at school, especially teacher discipline, is also an important factor affecting learning effectiveness. Although teacher attendance is relatively high, efforts to improve attendance and the quality of teacher professionalism need to be improved. Professional training organized periodically by schools is a strategy to help improve teachers' competencies, but funding constraints are still a major issue that needs to be addressed. Evaluation of teachers' job satisfaction is also an important aspect that needs to be considered in improving their motivation and performance in teaching students. Support from various parties is needed including school administrators, teachers and TU staff